The Neglected Modern Architectural Heritage: Analysis of Housing Estates in the Second Half of the 20th Century from Izmir, Turkey, Case Study Area - Gizem Güler Nakıp; Magdalena Żmudzińska-Nowak; Gülnur Ballice (Buildings)
Twentieth-century housing estates are an important part of the architectural heritage of the modern age, reflecting not only the evolution of housing forms, but also the technological advances and sociocultural dynamics of the twentieth century. However, awareness of the value of this heritage is still insufficient, resulting in a lack of legal protection and numerous threats in the form of transformation and negligence. In this research, we present the problem using the example of modernist Turkish architecture. The settlements of Izmir, a cosmopolitan port city with a diverse socio-cultural fabric and rapidly developing housing architecture, are chosen as the subject of the study. The main objective of the study is to evaluate the state of conservation and the degree of transformation of the selected estates. The overall assessment of the maintenance of the legibility of urban layouts and the form of individual buildings shows that, despite the lack of systematic protection, it is possible to preserve the existing architectural heritage in the examples analyzed and to provide recommendations for future policies to sustain the heritage values of modernism. The research aims to fill the existing gaps in the discourse on modern housing and contribute to a broader international dialogue on the conservation of modern architecture. By including these estates in the ongoing discussion, we recognize their historical significance and promote their preservation as important participants in contemporary urban life.